How teachers develop content literacy of their students and use children’s literature for such purposes - Enkelena Shockett-Qafleshi (Universitat Autònoma de Barcelona, 2011)
This article centers round significant issues such as how children's literature supports the development of content literacy of students and what content literacy implies in itself. Based on a case study in a children's literature class, the author first defines content literacy, then outlines how mismatches in the classes derived from different cultural backgrounds of the students can influence the development of literacy in school. The article provides a brief analysis of classroom data followed by a proposal for developing students' content literacy development when they are asked to work with a novel; appropriate strategies to establish reading and writing comprehension of classic novels (in this case study"Treasure Island") in order to motivate students; how to develop activities aimed at helping students improve their analytical reading and writing skills; and how to sharpen children's self - regulated learning skills.